(t*y'(t))' = t*Dirac(t-2), t>0(adsbygoogle = window.adsbygoogle || []).push({});

we know that y(t) = 1 lim t--> o+

solve for y(t)

the solution says that by using

f(t)*Dirac_a(t) = f(a) * Dirac_a(t) we get

(t*y'(t))' = 2*Dirac(t-2) Dont see how they get that

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Hard D.E

**Physics Forums | Science Articles, Homework Help, Discussion**